Administrative Passages - Armstrong, Denise. author. aut Link
XXIV, 152 p.
Keywords: Assistant principals are vital to school success. As one of the largest groups of frontline managers, they represent the face of school administration and they perform a complex range of leadership and managerial roles. As important as they are, little academic attention has been directed to the role of the assistant principal and the ways in which newcomers navigate the transition from teacher to effective administrator. This book addresses this gap by offering a perspective on administrative practice which is not normally discussed in traditional textbooks. It describes the socio-emotional journey from teaching to administration through the eyes of eight newly appointed secondary school assistant principals, and it introduces a change model which integrates literature and primary research. The assistant principals’ narratives open a new window onto the inner and outer world of schools, revealing an uncharted landscape of paradoxes and emotions. These stories also uncover hidden boundaries, rites, and rituals which operate beneath a veneer of order, control, and stability, and shape administrators’ work lives in imperceptible ways. As the new assistant principals describe their dreams, disappointments, and accomplishments, they illustrate the complex challenges of leading and learning within shifting organizational contexts. This book will be of interest to practitioners, policy makers, and theoreticians alike. It provides practical advice on surviving this career passage, and it identifies how institutional processes, policies, and practices can be improved to support this important leadership role. This book offers terrific insights into the different challenges one faces in adjusting to the role of the Assistant Principal, and will provide readers with a rich array of strategies regarding the mental, emotional, social, and physical adjustments required for a successful transition. ProfessorEmeritus William D. Greenfield, Jr., Portland State University, USA Professor Armstrong provides a comprehensive review of vice principals’ career transitions and introduces a compelling new model for understanding the journey from teacher to administrator. Theory is brought to life and readers gain fascinating insights into the challenges which new vice-principals - real people – experience in the transition from teaching to administration. Dr. Chris Spence, Director, Toronto District School Board, Canada The few books currently available on the role of the assistant principal tend to be thin little survival guides aimed at practitioners working in the sink or swim environment of a new appointment. All the more reason to celebrate the publication of this substantial new book that skillfully addresses the craft knowledge and phenomenology of the transition from teaching to school administration roles, and does so in a scholarly manner –integrating relevant theory and research within an inspired and memorable conceptual framework of epicycles. The outcome is nothing short of ground breaking. This is an important new addition to the literature on the processes of professional socialization. Professor Paul Begley, Penn State University, USA.